Solutions to restrictions of the current conveyor based circuits - Yüce, Erkan. (Thesis (Ph.D.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2006., 2006)
Current conveyor (CC) is one of the most widely used versatile active components. It potentially provides higher accuracy, wider bandwidth, greater linearity and larger dynamic range. The advantages of the CCs have brought widespread usage in some technical areas such as current-mode analog communication systems and signal processing. It was initially proposed by Sedra and Smith in 1968. A modified version is presented as a second-generation current conveyor (CCII) in 1970. The CCII continues to receive much more attention, and finds numereous applications in many fields of electronics. This growing interest to the CC has led us to focus on this basic building block and its extensively used applications such as simulated inductors and active analog filters. Inductors are not desirable passive elements in most electronic circuits because the behavior of them is not very close to the ideal element behavior and they are physically larger and heavier than other components. In addition, it is very difficult to realize large-valued inductors in integrated circuit (IC) technology and maximum a few nH inductors with low Q can only be implemented with current technology. Instead of large-valued physical inductors, simulated inductors employing CCs or other active components are widely used in many analog circuits. Such inductors with capacitors and other components can be used to form tuned circuits to build filters. CC based circuits suffer from several restrictions such as parasitic impedance and frequency dependent non-ideal gain effects in addition to signal limitations stemmed from the restricted DC power supply voltages and limited allowable input currents. In fact, such restrictions also exist in other circuits realized with different active building blocks. The mentioned limitations usually result in some undesired conditions such as stability problems and distortions at the output terminals. In this thesis, the restrictions of the CC based current-mode and voltage-mode analog filters as well as simulated inductors that can be used as building blocks for analog filtering functions are investigated in detail. Throughout this thesis, some methods to overcome these restrictions have been proposed. A number of novel simulated inductors and analog filters with reduced parasitic impedance effects are presented as alternative circuits. Several experimental results using the commercially available active devices, AD844s are shown. Moreover, time and frequency domain as well as Monte Carlo analysis using SPICE and MATLAB programs are performed to verify the theory of the designed inductors and analog filter circuits.
Keywords: Direct current amplifiers.